Enhancing School diets through climate-smart vegetable production - Coyne, D.L.; Kisaakye, James; Njeri, Ann; Nyambura, Eva Ivy; Miringu, Newton Nyagah; Odera, Janet Achieng; Irungu, Miriam; Nyabuto, Mellen; Awino, Martha (CGIAR System Organization, 2025)
With rapid urbanization, schools remain an untapped frontier for building a resilient urban food system. In 2024, a survey conducted by Global Child Nutrition Foundation (GCNF) found that approximately 400 million children globally depend on school feeding programs addressing hunger and child malnutrition in around 148 countries. Currently, school feeding programs have grown significantly in Kenya, and according to Food for Education, 450,000 children currently depend directly on school feeding program meals daily.